2012
DOI: 10.1002/pi.4291
|View full text |Cite
|
Sign up to set email alerts
|

Modified resistivity–strain behavior through the incorporation of metallic particles in conductive polymer composite fibers containing carbon nanotubes

Abstract: Eutectic metal particles and carbon nanotubes are incorporated into a thermoplastic polyurethane matrix through a simple but efficient method, melt compounding, to tune the resistivity–strain behavior of conductive polymer composite (CPC) fibers. Such a combination of conductive fillers is rarely used for CPCs in the literature. To characterize the strain‐sensing properties of these fibers, both linear and dynamic strain loadings are carried out. It is noted that a higher metal content in the fibers results in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(43 citation statements)
references
References 44 publications
0
41
0
Order By: Relevance
“…Here, a gauge factor (GF = (DR/R 0 )/e, where DR/R 0 is the responsivity of the porous CPC foam and e is the compression strain) can be introduced to evaluate the sensitivity of the strain sensor. 4,36,60 It can be seen that the GFs at the strain rates of 1, 3 and 5 mm min À1 are about 0.82, 1.28 and 2.32, respectively, indicate that a higher strain rate brings about higher strain sensitivity. This is mainly because that the porous CPC foam suffered a larger compression stress at a higher compression rate (Fig.…”
Section: Piezoresistive Behavior Of Porous Graphene/tpu Foamsmentioning
confidence: 93%
See 1 more Smart Citation
“…Here, a gauge factor (GF = (DR/R 0 )/e, where DR/R 0 is the responsivity of the porous CPC foam and e is the compression strain) can be introduced to evaluate the sensitivity of the strain sensor. 4,36,60 It can be seen that the GFs at the strain rates of 1, 3 and 5 mm min À1 are about 0.82, 1.28 and 2.32, respectively, indicate that a higher strain rate brings about higher strain sensitivity. This is mainly because that the porous CPC foam suffered a larger compression stress at a higher compression rate (Fig.…”
Section: Piezoresistive Behavior Of Porous Graphene/tpu Foamsmentioning
confidence: 93%
“…6 Meanwhile, it has also been demonstrated that the conductive network distributed in the polymer matrix could be tuned by changing the loading or the type of conductive fillers, causing different sensing behaviors. 11,36 Carbon based conductive materials such as carbon black, CNTs and graphene are the most frequently used fillers to fabricate CPCs. In particular, the single layer two dimensional graphene has been considered as a good candidate.…”
Section: à3mentioning
confidence: 99%
“…Such a huge interest may be owned to its novel properties like high modulus and tensile strength, large theoretical specific surface area, almost transparent and excellent conductivity. Out of many possible functionalized forms of graphene and its composites, polymer-based graphene composites are quite promising candidates due to combined improved properties [8]. A flexible supercapacitor is one of the most important energy storage devices which have been extensively explored in these years [9].…”
Section: Introductionmentioning
confidence: 99%
“…These composites are prepared by compounding the polymer and conductive nanoparticles (such as carbon black, carbon nanotubes, carbon fiber, graphite and metal particles) [1,2]. When the content of conductive nanoparticle reaches to a critical value (i.e.…”
Section: Introductionmentioning
confidence: 99%